Optimization of Participatory and Collaborative Planning Methods for Accelerating the Preparation of Detailed Spatial Plans - Santo, Deni; Achsani, Noer Azam; Rustiadi, Ernan; Buono, Agus (BHUMI: Jurnal Agraria dan Pertanahan, 2023)
The availability of Detailed Spatial Plans (RDTR) is crucial for supporting development implementation and ease of doing business. However, there are still problems in the preparation of RDTR, necessitating acceleration. Regarding this acceleration, it is necessary to analyze how participatory and collaborative planning methods can play a role. Participatory and collaborative approaches are important because public trust and stakeholder relationships in participatory and collaborative planning influence the implementation process and planning outcomes. This study aims to identify the relationships between implementing actors and stakeholders involved in the preparation of RDTR so that they can be optimized with a participatory and collaborative approach. The research methods used are Social Network Analysis (SNA), Organizational Network Analysis (ONA), and post-review surveys. The results show that the relationships between implementing actors and stakeholders related to RDTR preparation are not yet optimal, therefore requiring remapping and rearrangement within the legal framework. Participatory and collaborative approaches will elaborate the possibility of more effective and efficient relationships with changes in roles and media of interaction. Keywords: Collaborative, Network Analysis, Participatory, RDTR, Spatial Planning